Case report: Local bleomycin injection: A possible treatment option for primitive myxoid mesenchymal tumor of infancy - Yang, Binbin; Chen, Qingjiang; Zhu, Yueling; Wang, Jianbing; Dong, Ao; Chen, Yi; He, Xue; Gu, Weizhong; Gao, Zhigang; Qian, Yunzhong (Frontiers in Pediatrics, 2022)
In recent years, it has been determined that primitive myxoid mesenchymal tumors of infancy (PMMTI) are solid tumors. To date, very few cases of PMMTI have been reported, and there is no consensus regarding treatment. To provide additional references, it is necessary to collect and report the diagnoses and treatment outcomes of related cases. We report the case of a 38-day-old girl who presented with a 5-cm purple tumor in the right shoulder. Upon hospital admission, the patient received an intratumoral injection of bleomycin after diagnosis of a possible lymphangioma. 10 days after the treatment, the tumor began to develop inflammation and necrosis, resulting in a clear demarcation between the tumor and surrounding tissue. Hence, during the second hospitalization, we performed a successful tumor resection. Postoperatively, the tumor was pathologically diagnosed as PMMTI. 3 months after excision, the patient showed no local recurrence on re-examination. To the best of our knowledge, this is the first report of a PMMTI in which bleomycin, or other similar chemotherapeutic drugs, have been injected into tumors. This result offers novel insights into the treatment of PMMTI. Injection therapy with bleomycin and similar chemotherapeutics may result in specific responses to PMMTI, which may help in developing better surgical conditions or improving outcomes in non-surgical patients.